A case of combined course of leptospirosis and coronavirus infection COVID-19 - E. L. Krasavtsev; V. I. Mаiseenko; O. A. Kozel; E. A. Kuchun (Журнал инфектологии, 2022)
A clinical case of a combined course of leptospirosis and coronavirus infection in a 71-year-old patient is presented. One of the features of this case was the difficulty of confirming the clinical diagnosis of leptospirosis in the absence of a typical clinical picture of this disease. Only the data of the epidemiological history and manifestations of the disease atypical for coronavirus infection allowed to suspect leptospirosis and confirm it by methods of specific laboratory diagnostics. The stages of differential diagnostic search in the practice of an infectious disease doctor are described.